2011
DOI: 10.1192/bjp.bp.110.080044
|View full text |Cite
|
Sign up to set email alerts
|

Disease-modifying properties of long-term lithium treatment for amnestic mild cognitive impairment: randomised controlled trial

Abstract: The present data support the notion that lithium has disease-modifying properties with potential clinical implications in the prevention of Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
245
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 322 publications
(261 citation statements)
references
References 26 publications
10
245
2
4
Order By: Relevance
“…A Phase II clinical trial studying the effect of lithium treatment in patients with AD is currently underway (ClinicalTrials.gov identifier: NCT00088387), and in a small cohort of patients lithium reduced the progression from mild cognitive impairment to full AD 55 . In addition to increasing BDNF levels, lithium also inhibits the hyperphosphorylation of Tau mediated by GSK3β and has additional beneficial effects in the activation of pro-survival CREB signalling and the activation of autophagy [56][57][58][59] ( Figure 2, and see below).…”
Section: Increasing Bdnf As a Therapeutic Approachmentioning
confidence: 99%
“…A Phase II clinical trial studying the effect of lithium treatment in patients with AD is currently underway (ClinicalTrials.gov identifier: NCT00088387), and in a small cohort of patients lithium reduced the progression from mild cognitive impairment to full AD 55 . In addition to increasing BDNF levels, lithium also inhibits the hyperphosphorylation of Tau mediated by GSK3β and has additional beneficial effects in the activation of pro-survival CREB signalling and the activation of autophagy [56][57][58][59] ( Figure 2, and see below).…”
Section: Increasing Bdnf As a Therapeutic Approachmentioning
confidence: 99%
“…Moreover, in individuals with mild cognitive impairment (MCI), we found that low-dose lithium intake over 4 years reduced the conversion to AD [31]. As MCI is considered a pre-Alzheimer condition [32], these findings suggest that lithium may have disease-modifying properties capable of reducing AD risk.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 86%
“…Barthel et al, using positron emission tomography (PET) images of florbetaben (an 18 F-labeled Aβ-targeted PET tracer), demonstrated that nine of ten mildmoderate probable AD participants (DSM-IV and NINCDS-ADRDA criteria) were Aβ-positive, compared to only one of ten healthy controls [49] . Furthermore, in a global phase 2, open-label, non-randomized, multi-center study recruiting a total of 81 men and women with probable mild-to-moderate AD and 69 cognitively unimpaired healthy volunteers aged 55 years and older, florbetaben scans indicated a sensitivity of 80% (95% CI 71-89) and a specificity of 91% (84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98) for discriminating participants with AD from healthy controls [50] .…”
Section: Aβ As a Promising Target For Ad Treatmentmentioning
confidence: 99%
“…The role of GSK-3 in the development of AD-like cognitive decline was supported by Liu et al [86] who found that inhibition of phosphoinositol-3 kinase and protein kinase C results in overactivation of GSK-3, leading to tau hyperphosphorylation and eventually impaired spatial memory. Lithium, a GSK-3 inhibitor, has been shown to reduce the amount of altered tau protein in animal studies and improve cognitive and biological outcomes in participants with amnestic mild cognitive impairment in a phase 2 clinical study [87] .…”
Section: Other Therapeutic Approaches To Admentioning
confidence: 99%
See 1 more Smart Citation